Dexmedetomidine upregulates microRNA-185 to suppress ovarian cancer growth via inhibiting the SOX9/Wnt/β-catenin signaling pathway - Tian, Hang (Cell Cycle, 2021)
Dexmedetomidine (DEX) could serve as an adjuvant analgesic during cancer therapies. Abnormal expression of microRNAs (miRNAs) could lead to cancer development. This study was aimed to explore the roles of DEX in ovarian cancer (OC) development. OC cell lines SKOV3 and HO-8910 were treated with DEX, after which OC development and the miR-185, SOX9, and Wnt/β-catenin pathway were measured. DEX-treated HO-8910 cells were transfected with miR-185 mimic, miR-185 antisense or miR-185 antisense + silenced SOX9 to further measure the OC cell growth. The target relation between miR-185 and SOX9 was identified, and SOX9 and Wnt/β-catenin pathway were protein levels detected after miR-185 transfection. The role of miR-185 in OC in vivo was also measured. Our study found DEX had a dose-dependent inhibition on OC growth, and DEX promoted miR-185 but suppressed SOX9 expression in OC cells. miR-185 targeted SOX9. After interfering with miR-185 expression, HO-8910 cell proliferation, invasion, migration, and apoptosis were affected. SOX9 knockdown repressed OC development and Wnt/β-catenin pathway. The volume, weight, positive rate of Ki67, CyclinD1, p53 and the degree of tumor necrosis were affected by miR-185 expression. This study demonstrated that DEX could inhibit OC development via upregulating miR-185 expression and inactivating the SOX9/Wnt/β-catenin signaling pathway.